The Appraisal of Eulogies Delivered at Mrs. Lee Kuan Yew Memorial Service - Maula, Inayatul; Sutopo, Djoko; Fitriati, Sri Wuli (Universitas Negeri Semarang, 2018)
The study reports the appraisal analysis and the rhetorical structure of eulogies delivered at Mrs. Lee Kuan Yew memorial service. Eulogies are meant to remember the person who died in a positive light, and offer an opportunity to speak about who the deceased was and the ways in which she or he made a difference in the lives of family, friends, and his or her community. Since eulogy contains praises for someone admired, and the speaker recalls the memories shared, he has to evaluate his feelings and relation by expressing attitude, his position towards the deceased, and gradable valuation. Such evaluation has to do with appraisal system. The research integrates the appraisal theory proposed by Martin and White (2005) and rhetorical structure (Kunkel and Dennis, 2003). This study employs discourse analysis method of research. The findings reveals that the eulogies have primarily used the judgement resources rather than affect and appreciation within the attitude system. As eulogizing function, the eulogy composed largely of laudation and praise, the use of judgement appraising items shows how the eulogizer’s assessment towards the admiring behaviour of the deceased during her life. Moreover, the utilization of the rhetorical structure contributes to the achievement of the communicative purpose of eulogy. Through the well-structured eulogies, the eulogizers heighten the audience member’s feelings of regard, love, and appreciation for the deceased.